Horizontal recycling of aluminum alloys for the Tokaido Shinkansen N700S - ITO, Jun; YOKOYAMA, Koji; FUJII, Tadashi (Kikai Gakkai ronbunshū = Transactions of the Japan Society of Mechanical Engineers, 2024)
Aluminum alloy double skin extruded materials are used for carbody and interior materials of the Tokaido Shinkansen rolling stock. In previous rolling stock (e.g. series 700 and series N700), all of these extrusions used alloys based on virgin aluminum ingots. In addition, the aluminum alloys obtained from discarded Shinkansen vehicles contain a mixture of 5000 series, 6000 series, and 7000 series alloys, so that these alloys have been cascade-recycled to acid agents, die casting mold, and not recycled to railway vehicles. This research is a multifaceted study on horizontal recycling to the same aluminum alloy types used in railway vehicles, as a part of efforts to reduce indirect CO2 emission in the supply chain under partnerships with the companies involved in the lifecycle of railway vehicles. As a result of the verification through the comparison and evaluation of prototypes, it was proved that it is possible to simplify the sorting process and establish a highly accurate and low-cost recycling method by implementing highly accurate separate dismantling in the dismantling process of discarded vehicles, which corresponds to the upstream process of recycling. By applying this recycling method to a part of the roof structure of Series N700S rolling stock of the Tokaido Shinkansen, it enabled to reduce CO2 emission by approximately 50 tons per trainset.